2011
DOI: 10.3390/ijms12053182
|View full text |Cite
|
Sign up to set email alerts
|

Mesomorphic Properties of an Homologous Series of Thioalkyl-Terminated Azomesogens

Abstract: A new homologous series (ten compounds) of 2-hydroxy azo compounds SRn (where n:1–10) were synthesized. Their structures were elucidated using spectroscopic techniques such as IR (Infrared), 1H-NMR as well as elemental analysis. Mesomorphic properties and phase transitions were studied using polarized hot stage optical microscopy and differential scanning calorimetry (DSC), and are discussed as a function of the number of carbon atoms in the thioalkyl chain. It has been found that all compounds in the series a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…[13][14][15][16][17] Liquid crystal materials bearing azo/ester central linkages and middle and terminal phenyl rings substituted with groups of different polarity as well as nalkoxy group on the other end of the molecule were reported. [18][19][20][21][22][23][24][25][26][27] In previous work [28] in this laboratory, the effect of compact terminal substituent (X), as well as the terminal alkoxy (RO-) group, of varying chain length, on the mesophase behaviour of compounds of the type 4-(4′-substituted phenylazo) phenyl 4″-alkoxybenzoates (IIn af ) was studied. In that work, [28] it was observed that the stability of the mesophase is augmented by an increase in the polarity and/or polarisability of the mesogenic part of the molecule, which is definitely affected by the polarity of the substituent, and its position, which would accordingly affect the polarity of the whole molecular structure by the way the polar substituents electronically interact with the remainder of the molecule.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17] Liquid crystal materials bearing azo/ester central linkages and middle and terminal phenyl rings substituted with groups of different polarity as well as nalkoxy group on the other end of the molecule were reported. [18][19][20][21][22][23][24][25][26][27] In previous work [28] in this laboratory, the effect of compact terminal substituent (X), as well as the terminal alkoxy (RO-) group, of varying chain length, on the mesophase behaviour of compounds of the type 4-(4′-substituted phenylazo) phenyl 4″-alkoxybenzoates (IIn af ) was studied. In that work, [28] it was observed that the stability of the mesophase is augmented by an increase in the polarity and/or polarisability of the mesogenic part of the molecule, which is definitely affected by the polarity of the substituent, and its position, which would accordingly affect the polarity of the whole molecular structure by the way the polar substituents electronically interact with the remainder of the molecule.…”
Section: Introductionmentioning
confidence: 99%